A2_2 Water on the Moon: an energy comparison - Rolfe, Samantha; Wilson, Mark; Evill, Ry; Johnson, Christopher (Physics Special Topics, 2009)
This paper discusses the implication of the LCROSS mission finding water-ice in a permanently shadowed crater on the Moon.Â If water-ice is discovered, through looking at a simple model of the crater, this paper looks at how useful the water-ice would be to future long-term missions by comparing the amount of energy needed to raise the ice from the surface of the Moon to transporting water from Earth. Â Assuming water-ice is present - even in the general case where the mission length and crew number is unspecified - to send sufficient water from Earth a factor of 108 J person-1 day-1 is required when compared to mining the ice.